Immobilized culture of nonadherent cells on an oleyl poly(ethylene glycol) ether-modified surface. (November 2003) - Kato, Koichi; Umezawa, Kohei; Funeriu, Daniel P.; Miyake, Masato; Miyake, Jun; Nagamune, Teruyuki
Microarrays of living cells are an emerging tool in systems such as reverse transfection. These studies are limited to adherent cells partly because of the difficulty of cell immobilization. Using a newly developed reagent, the biocompatible anchor for membrane (BAM), we show herein the rapid and strong attachment of living nonadherent cells and adherent cells on BAM-modified surfaces. Normal cellular growth was observed for over 7 days on BAM-modified surfaces. We expect this methodology to greatly expand the scope of current cell microarray technology.